1998
DOI: 10.1902/jop.1998.69.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Guided Tissue Regeneration Using 4 Barrier Membranes: A Comparative Furcation Study in Dogs

Abstract: This study evaluated and compared four different barrier membrane materials used to treat class II mandibular premolar and molar furcations in seven dogs with naturally occurring periodontitis. Five class II furcation defects in each animal were randomly assigned to one of four experimental groups or to a control group. Each defect was treated by surgical debridement, root planing, and barrier membrane coverage with one of the four test materials or no barrier membrane (control). Thus, each animal served as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…This result is consistent with that found by Deliberador et al (2006), in which the control treatment group made with calcium sulfate membranes showed high diffuse inflammatory infiltration. Lekovic et al (1998), in a study of four membranes, one of polycaprolactone, results showed a good formation of cementum and alveolar bone, however, the membrane comprising polycaprolactone showed high inflammatory response, as seen in the present study. Figure 6.…”
Section: Resultssupporting
confidence: 65%
“…This result is consistent with that found by Deliberador et al (2006), in which the control treatment group made with calcium sulfate membranes showed high diffuse inflammatory infiltration. Lekovic et al (1998), in a study of four membranes, one of polycaprolactone, results showed a good formation of cementum and alveolar bone, however, the membrane comprising polycaprolactone showed high inflammatory response, as seen in the present study. Figure 6.…”
Section: Resultssupporting
confidence: 65%
“…In contrast, the pathogenesis of natural periodontal lesions in canines closely resembles the human situation and represents the animal disease model closest to humans in terms of healing and pathogen-associated microbiota (Syed et al, 1981;Giannobile et al, 1994;Madianos et al, 1994). Natural periodontal lesions have been used to test the effects of biologics such as growth factors and barrier membranes on periodontal regeneration (Lynch et al, 1991;Giannobile et al, 1994;Lekovic et al, 1998). Histomorphometric endpoints include the area or height of newly formed bone, cementum, complete new attachment formation (new bone cementum and PDL; CNAA), osseous defect fill, root resorption, and ankylosis.…”
Section: Canine As Large Animal Defect Model Natural Periodontal Lesionsmentioning
confidence: 99%
“…Furthermore, periodontal diseases can be easily induced in dogs. [12][13][14][15][16] Although subgingival plaque formation in dogs may not develop identically to that in humans, dogs may still serve as a conventional model for investigation.…”
mentioning
confidence: 99%